PENGARUH KEMUDAHAN DAN FITUR LAYANAN TERHADAP MINAT MENGGUNAKAN E-WALLET PADA PEMBAYARAN AIR PDAM TIRTANADI - Hanum, Zubaidah; Hasibuan, Siska; Habibah, Jaurah (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This research discusses the influence of convenience and service features on interest in using e-wallet when paying for PDAM Tirtanadi water. Carrying out this objective aims to determine the influence of convenience (X1) and service features (X2) on interest in using (Y). Each variable from this research has an indicator. The Convenience indicator (X1) is easy to learn, controllable, flexible, easy to use, clear and understandable. Indicators of Service Features (X2) are ease of access to product or service information, diversity of transaction services, diversity of features, product innovation. Indicators of Interest in Using (Y) are will transact, will recommend, will continue to use. This research has 70 populations and 70 samples using quantitative methods. For processing research data using the SPSS 26 program. Based on the research results, it can be seen that the convenience variable and the service feature variable partially have a significant effect on the interest variable in using it. This conclusion is proven by the results of the T test which has a calculated t value of 4.806 > t table 1.667 and the significant value is 0.000 <0.05. The results of the normality test show that the data is normally distributed, obtaining results > 0.05. The results of the multicollinearity test showed that there were no deviations in the two independent variables, obtaining a VIF value < 5 (2.244 < 5). The results of the heteroscedasticity test show that the Sig. > 0.05 which indicates that heteroscedasticity does not occur. The results of the multiple linear regression test have the equation Y = 2.520 + 0.328 X1 + 0.282 X2. The results of the coefficient of determination test (R Square) obtained a value of 0.785 (78.5%), which means that the variables of convenience and service features have an influence on interest in using by 78.5%.